Safe Spaces for Immersive Safety Training in Virtual Reality: A Phenomenological Conceptualization - Haj-Bolouri, Amir (International Journal of Virtual Reality, 2024)
Immersive Virtual Reality (IVR) technology has been shown to effectively facilitate fire safety training. However, the current discourse on immersive safety training provides scarce knowledge on the quality of immersive safety training from the perspective of safe spaces. In turn, the general notion of a safe space – being an environment that is characterized by the freedom to move, share, talk, and act freely without risk for physical or mental damage – needs further elaboration in an IVR training context where the experience of safety is highly interrelated with embodiment and immersion. This study employed thus a phenomenological approach to explore and conceptualize characteristics of immersive safe spaces. This was done through phenomenological interviews with employees at Sweden’s largest train operating company, which undertook fire safety training in IVR by using an IVR application known as the “Fire Trainer”. The interview material was then analyzed through an Interpretative Phenomenological Analysis (IPA) that conceptualized four themes for characterizing immersive safe spaces: Sense of Authentic Hazard Recognition, Sense of Behavioral Responsiveness, Sense of Intersubjective Risk Perception, and Sense of Embodied Atmosphere. Implications of conceptualizing the themes are targeted towards understanding the quality of being/feeling safe during safety training in IVR, and how the design of future immersive fire safety environments might benefit from employing the proposed themes.